PENERAPAN PERMAINAN â€œAKU PEMBURU POKEMONâ€ UNTUK MENINGKATKAN KETERAMPILAN MENULIS SURAT UNDANGAN RESMI (Penelitian Tindakan Kelas di Kelas V-B SDN Conggeang 1 Kecamatan Conggeang Kabupaten Sumedang) - Komalasari, Ala; Iswara, Prana Dwija; Gusrayani, Diah (Jurnal Pena Ilmiah, 2017)
This study aims to improve the skills of writing official invitation letter students by applying the game â€œAku Pemburu Pokemonâ€. This research was conducted in three cycles, using research of class action model of Kemmis and Taggart covering the stage of planning, implementationand observation and analysis and reflection. The result show that the game â€œAku Pemburu Pokemonâ€ can increase student participation during the learning activities take place, increase student cooperation with friends, and increase the motivation of student to continue to practice their ability in writing official invitation letter. This resulted in student activity increased to 95% in the third cycle. In addition to student activity, the learning result also increased by 95% in the third cycle. This is the result of teacher performance in planning and implementing learning that reaches 100% in third cycle.